KAJIAN ALTERNATIF TEKNOLOGI DESALINASI DALAM PRODUKSI AIR TAWAR UNTUK DESA LABUAN BAJO, NTT - Ersa, Ghina Rizqina (Department of Environmental Engineering-Faculty of Civil, Planning, and Geo Engineering. Institut Teknologi Sepuluh Nopember, Surabaya, 2020)
The increase in population number resulting in a higher clean water demand. Meanwhile water pollution from human activities continue to occur decreasing the quality of surface water sources. Another problem is seawater intrusion that contaminating the ground water. This study aims to suggesting the right innovation to resolve clean water crisis in Indonesia. Various technology such as Multi-Effect Distillation (MED), Multi-Stage Flash Distillation (MFD), Vapor Compression (VC), Reverse Osmosis (RO), and Electrodialysis have been developed. Another alternative is biodesalination process using mangrove, bacteria, and the combination of both mangrove and bacteria. Labuan Bajo village as one of the nation’s tourism destination, has a poor clean water supply system. From the discussion of this case study can be conclude that RO can be used as desalination technology for domestic and non-domestic clean water supply in Labuan Bajo village. The village can utilize Batu Gosok beach as the raw water resource. Desa Labuan Bajo dapat menggunakan Pantai Batu Gosok sebagai sumber air baku. The production debit that is needed to supply domestic and non-domestic clean water is 720 m3/day. Based on the study result the suitable desalination to be implemented in Labuan Bajo village in reverse osmosis.